Parkinson’s Disease Is Associated With Dysregulation of Circulatory Levels of lncRNAs - Honarmand Tamizkar, Kasra; Gorji, Pooneh; Gholipour, Mahdi; Hussen, Bashdar Mahmud; Mazdeh, Mehrdokht; Eslami, Solat; Taheri, Mohammad; Ghafouri-Fard, Soudeh (Frontiers in Immunology, 2021)
Long non-coding RNAs (lncRNAs) have been recently reported to be involved in the pathoetiology of Parkinson’s disease (PD). Circulatory levels of lncRNAs might be used as markers for PD. In the present work, we measured expression levels of HULC, PVT1, MEG3, SPRY4-IT1, LINC-ROR and DSCAM-AS1 lncRNAs in the circulation of patients with PD versus healthy controls. Expression of HULC was lower in total patients compared with total controls (Expression ratio (ER)=0.19, adjusted P value<0.0001) as well as in female patients compared with female controls (ER=0.071, adjusted P value=0.0004). Expression of PVT1 was lower in total patients compared with total controls (ER=0.55, adjusted P value=0.0124). Expression of DSCAM-AS1 was higher in total patients compared with total controls (ER=5.67, P value=0.0029) and in male patients compared with male controls (ER=9.526, adjusted P value=0.0024). Expression of SPRY4-IT was higher in total patients compared with total controls (ER=2.64, adjusted P value<0.02) and in male patients compared with male controls (ER=3.43, P value<0.03). Expression of LINC-ROR was higher in total patients compared with total controls (ER=10.36, adjusted P value<0.0001) and in both male and female patients compared with sex-matched controls (ER=4.57, adjusted P value=0.03 and ER=23.47, adjusted P value=0.0019, respectively). Finally, expression of MEG3 was higher in total patients compared with total controls (ER=13.94, adjusted P value<0.0001) and in both male and female patients compared with sex-matched controls (ER=8.60, adjusted P value<0.004 and ER=22.58, adjusted P value<0.0085, respectively). ROC curve analysis revealed that MEG3 and LINC-ROR have diagnostic power of 0.77 and 0.73, respectively. Other lncRNAs had AUC values less than 0.7. Expression of none of lncRNAs was correlated with age of patients, disease duration, disease stage, MMSE or UPDRS. The current study provides further evidence for dysregulation of lncRNAs in the circulation of PD patients.